Factors influencing the diagnostic and prognostic values of circulating tumor cells in breast cancer: a meta-analysis of 8,935 patients - Zhao, Hongfang; Wang, Luxuan; Fang, Chuan; Li, Chunhui; Zhang, Lijian (Frontiers in Oncology, 2023)
Background: Circulating tumor cell (CTC) could serve as predictive biomarker in breast cancer (BC). Due to the high heterogeneity, the diagnosis and prognostic values of CTC is challenging.We searched published studies in PubMed, Cochrane Library, Embase and MEDLINE database. The detection capability and hazard ratios (HRs) of CTC were extracted as the clinical evaluation size. Subgroup analyses were divided by the detection methods, continents, treatment periods, therapeutic plans and cancer stage.Results: Results: In this study, 35 publications have been retrieved with 8,935 patients enrolled. The diagnostic efficacy of CTC detection with 74% sensitivity and 98% specificity. The positive CTC detection would predict worse OS and PFS/DFS in both and mid-therapy and posttherapy (HROS, 3.09; 95% CI, 2.17-4.39; HRPFS/DFS, 2.06, 95% CI, 1.72-2.47). Moreover, CTC+ suggested poor survival irrespective of the treatment phase, and sampling time (HROS, 2.43; 95% CI, 1.85-3.19; HRPFS/DFS, 1.82; 95% CI, 1.66-1.99). The CTC+ was associated with poor survival regardless of the continents of patients (HROS = 2.43, 95% CI, 1. 85-3.19).Our study suggested CTC+ was associated with a worse OS and PFS/DFS in Asian population. And the detection method, threshold level of CTC+, therapeutic approaches and sampling time could not affect its diagnostic and prognostic values.